Regulation of progesterone receptor signaling by BRCA1 in mammary cancer - Katiyar, Pragati (The Nuclear Receptor Signaling Atlas, 2006)
Inherited mutations of the BRCA1 gene (chromosome 17q21), a tumor suppressor, lead to an increased risk of breast cancer, ovarian cancer, and several other hormone-responsive tumor types. Over the last ten years, BRCA1 has been found to play major roles in DNA damage signaling, repair, and cell cycle checkpoints. In addition, unfolding evidence suggests that BRCA1 functions as a co-regulator for steroid hormone receptors and modulates steroid hormone action. In this paper, we will briefly review this evidence and present a model to address the role of the progesterone and estrogen receptors in BRCA1 mutant mammary carcinogenesis. Finally, we will consider some of the clinical implications of this model.